Upaya Peningkatan Keterampilan Passing Bawah Melalui Model Problem-Based Learning Dengan Pendekatan Pembelajaran Berdiferensiasi Pada Peserta Didik Kelas XI APL 2 SMK Negeri 4 Pontianak - Lauh, Whalsen; Irawan, Heri; Syabid, Achmad; Purnama Sari, Ella; Mubarok, Riski; Ariyanta, Ariyanta (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2025)
This classroom action research (CAR) aims to improve student learning outcomes in underhand passing skills in volleyball through the implementation of the Problem-Based Learning (PBL) model with a Differentiated Instruction approach in class XI APL 2 at SMK Negeri 4 Pontianak. The research involved 31 students, consisting of 27 female and 4 male students from class XI APL 2. This study is a lesson study-based classroom action research conducted in collaboration with the physical education (PJOK) subject teacher, pre-service PPG students, and field supervisors. The research was carried out in two cycles, with each cycle following the three phases of lesson study: planning (plan), implementation (do), and reflection (see). The findings indicate an increase in the percentage of classical learning mastery from 61.3% in the first cycle to 83.8% in the second cycle. This improvement demonstrates that the implementation of the Problem-Based Learning model with a Differentiated Instruction approach can enhance students’ underhand passing skills in PJOK subject for class XI APL 2